An Analysis of Qualitative Open Defecation Behavior of North Maluku Province in 2017 (A Case Study at Community of Toseho Village in Archipelago Tidore City) - Norma B Toduho; Bambang Setiaji; Ratu Ayu Dewi Sartika (UHAMKA Press, 2019)
Background : Public Health Development Index in 2013, the correct behavior of defecation in North Maluku is about 0.78 percent and the rest still have Open Defecation Behavior.Purpose : The purpose of this research is to find out the Open Defecation Behavior (Case Study at Community of Toseho Village in Tidore Kepulauan City) in North Maluku Province.Methods : The methods used are observation, in-depth interview, and FGD (Focus Group Discussion). Determinant of informants used